ANALISIS GAYA BAHASA PADA NOVEL DIA YANG HARAM KARYA ISRINA SUMIA - Wa Ode Rostika; Sumiman Udu; La Tike (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
This study aims to describe the types of figurative language found in the novel Dia yang Haram by Isrina Sumia. The focus of this research is on comparative and associative figurative language used by the author to enhance the expressive and aesthetic qualities of the narrative. The method used is descriptive qualitative with a stylistic approach. Data were collected through reading, note-taking, and analyzing excerpts in the novel that contain stylistic elements. The results show that the dominant types of comparative figurative language include simile, metaphor, personification, allegory, antithesis, pleonasm, periphrasis, and epanorthosis. Meanwhile, the associative figurative language consists of metonymy, synecdoche, allusion, euphemism, eponym, epithet, and antonomasia. These figurative expressions serve to emphasize character emotions, clarify situations, and enrich the artistic value of the novel. This study contributes to literature teaching and the understanding of stylistics in fictional works.